2010
DOI: 10.1016/j.bbmt.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-Host Disease: Role of Inflammation in the Development of Chromosomal Abnormalities of Keratinocytes

Abstract: Graft-versus-host disease (GVHD) is a major risk factor for secondary malignancy after hematopoietic stem cell transplantation. Squamous cell carcinoma (SCC) of the skin and mucous membranes are especially frequent in this setting where aneuploidy and tetraploidy are associated with aggressive disease. The current study is directed to the mechanism of neoplasia in this setting. Un-manipulated keratinocytes from areas of oral GVHD in 9 patients showed tetraploidy in 10–46% of cells when examined by florescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…The rarity of TP53 mutation herein confirms previous findings in three cases of HSCT/SCC showing the absence of TP53 mutation in exons 5-9 (Zhang et al, 2002). Our results in LPLE are also in accordance with an in vitro GVHD model, where keratinocytes showed no mutations in TP53 (Sloand et al, 2010).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The rarity of TP53 mutation herein confirms previous findings in three cases of HSCT/SCC showing the absence of TP53 mutation in exons 5-9 (Zhang et al, 2002). Our results in LPLE are also in accordance with an in vitro GVHD model, where keratinocytes showed no mutations in TP53 (Sloand et al, 2010).…”
supporting
confidence: 91%
“…TP53 copy-number alterations, whether TP53 haploinsufficiency or an increased TP53 allele copy number, were found in all LPLE-HSCT/SCC sequences, as described in different malignancies, where TP53 allele deletion can be associated with p53 accumulation without TP53 mutation (Brito-Babapulle et al, 2000;Saeki et al, 2011). These findings are in accordance with the high rate of genomic instability in oral mucosa after HSCT (Khan et al, 2010) and with the common haploinsufficiency for TP53 due to the loss of chromosome 17 in keratinocytes in an in vitro GVHD model (Sloand et al, 2010). Such genomic instability may be due to chronic nitric oxide release and/ or to replication stress.…”
supporting
confidence: 82%
“…In an in vitro mutation analysis system, we found that allostimulated mixed lymphocyte cultures may induce MSI in co-cultured epithelial cells [22]. These results were independently confirmed by subsequent studies from other groups, which reported that the detection of MSI [23] and chromosomal instability [24] in the epithelial tissues of patients after allo-HSCT was correlated to the presence of GvHD inflammation.…”
Section: Introductionsupporting
confidence: 70%
“…34 Surveillance for secondary cutaneous tumors Conditioning regimens and prolonged immunosuppression increases the risk of secondary malignancies of the skin including SCC, basal cell carcinoma, and melanoma. 17,[35][36][37]38 The long-term risk of melanoma in pediatric patients receiving HCT may be associated with a conditioning regimen using high doses of alkylating drugs. 36 Patient age, actinic exposure, skin phototype, and previous ionizing radiation are additional risk factors in the development of nonmelanoma skin cancers after HCT 39,40 (Fig 3).…”
Section: Wound Managementmentioning
confidence: 99%